A third HSAN5 mutation disrupts the nerve growth factor furin cleavage site - Shaikh, Samiha S (Mol Pain, 2018)
Bi-allelic dysfunctional mutations in nerve growth factor (NGF) cause the rare human phenotype hereditary sensory and autonomic neuropathy type 5 (HSAN5). We describe a novel NGF mutation in an individual with typical HSAN5 findings. The mutation c.361C>T, p.R121W is at the last residue of the furin cleavage motif Arg-Ser-Lys-Arg in proNGF. We show that the p.R121W mutation completely abolishes the formation of mature NGF-β. Surprisingly, mutant p.R121W cells produced very little proNGF. Instead, the two progressive cleavage products of proNGF were produced, proA-NGF and proB-NGF, with proB-NGF being the predominant NGF-derived peptide and the only peptide secreted by mutant p.R121W cells. We found that the ability of the p.R121W mutation to cause tropomyosin receptor kinase A autophosphorylation and mitogen-activated protein kinase phosphorylation was significantly reduced compared to controls (p < 0.05 and p < 0.01). By studying the PC12 cell line morphology and neurite length over a week, we found the p.R121W mutation had residual, but much reduced, neurotrophic activity when compared to wild-type NGF. Finally, we assessed whether the p.R121W mutation affected apoptosis and found a reduced protective effect compared to wild-type NGF. Our results suggest that the p.R121W NGF mutation causes HSAN5 through negating the ability of furin to cleave proNGF to produce NGF-β.